2008
DOI: 10.1089/hyb.2008.0017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Anti-podoplanin Monoclonal Antibodies: Critical Epitopes for Neutralizing the Interaction Between Podoplanin and CLEC-2

Abstract: Podoplanin (Aggrus) is a mucin-type sialoglycoprotein that is known as a useful marker for lymphatic endothelium and tumor-initiating cells (TICs). Interaction between podoplanin and C-type lectin-like receptor-2 (CLEC-2) is reported to be critical for podoplanin-induced platelet aggregation and cancer metastasis. Recently, several anti-human podoplanin antibodies have been created; however, these anti-podoplanin antibodies have not been well characterized. Five anti-podoplanin antibodies (NZ-1, D2-40, AB3, 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 24 publications
2
69
0
Order By: Relevance
“…36 In addition, we confirmed that the PDPN-mediated adhesion was calcium dependent without any expressional switching All data are means±s.e. from triplicate experiments.…”
Section: Discussionsupporting
confidence: 68%
“…36 In addition, we confirmed that the PDPN-mediated adhesion was calcium dependent without any expressional switching All data are means±s.e. from triplicate experiments.…”
Section: Discussionsupporting
confidence: 68%
“…14 The membranes were incubated with an anti-human podoplanin antibody (NZ-1; AngioBio, Del Mar, CA) 30 or an anti-␤-actin antibody (Sigma, St. Louis, MO), followed by a horseradish peroxidase-conjugated secondary antibody, and developed using the ECL system (GE Healthcare, Chalfont St. Giles, Buckinghamshire, England, UK).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The podoplanin is a main factor for platelet aggregation induced by the glioblastoma cell line LN319 and a NZ-1 antibody for the PLAG domain completely inhibits podoplanin-induced platelet aggregation because of the neutralization between podoplanin and CLEC-2 [58,61]. In an experimental mouse model podoplanin promoted hematogenous metastasis to the lung and the antipodoplanin antibody NZ-1 suppressed both the podoplanin-CELC-2 interaction and podoplanin-induced pulmonary metastasis [59,61,64,65]. Possibility of the clinical application on the neutralization of podoplanin-CLEC-2 interaction inducing hematogenous metastasis should be settled early.…”
Section: Molecular Biological Function Of Podoplaninmentioning
confidence: 99%